2004
DOI: 10.1080/00039420410001701404
|View full text |Cite
|
Sign up to set email alerts
|

Performance of rabbits and oxidative stability of muscle tissues as affected by dietary supplementation with Oregano essential oil

Abstract: The effect of dietary supplementation with oregano essential oil on the performance of rabbits, and the susceptibility of the produced raw and thermally treated muscle tissue to lipid oxidation during refrigerated storage, were investigated. A total of 96 weaned rabbits were separated into four equal groups with three subgroups each. One group was given the basal diet and served as control, two groups were administered diets supplemented with oregano essential oil at levels of 100 and 200 mg/kg diet, whereas t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
52
1
18

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 28 publications
7
52
1
18
Order By: Relevance
“…Ibrahim et al (2000Ibrahim et al ( , 2002 reported a significant increase in body weight, average daily gain, and feed intake, with a slight improvement in feed conversion index in weaned rabbits fed a dietary supplement with basil (Ocimum basilicum), oregano (Origanum vulgare) and/or sage (Salvia officinalis) extracts. Botsoglou et al (2004) and Omer et al (2010), however, did not find any significant variations in growth rate in weaned rabbits given a feed supplemented with antioxidant activity extracts.…”
Section: Body Weight (Kg)mentioning
confidence: 92%
“…Ibrahim et al (2000Ibrahim et al ( , 2002 reported a significant increase in body weight, average daily gain, and feed intake, with a slight improvement in feed conversion index in weaned rabbits fed a dietary supplement with basil (Ocimum basilicum), oregano (Origanum vulgare) and/or sage (Salvia officinalis) extracts. Botsoglou et al (2004) and Omer et al (2010), however, did not find any significant variations in growth rate in weaned rabbits given a feed supplemented with antioxidant activity extracts.…”
Section: Body Weight (Kg)mentioning
confidence: 92%
“…Regarding oregano and sage extracts, there are no other comparable studies concerning rabbits and/or their carcass composition, but several other investigations have been carried out on other animals. Botsoglou et al(2004) presented the antioxidant effect of oregano essential oil on lipid oxidation in rabbits MLD.…”
Section: Resultsmentioning
confidence: 99%
“…(Lewis et al 2003;Lauková et al 2006;Marcin et al 2006;Simonová et al 2008). While most of the studies deal with the moderating effects of the environmental, feeding, genetic, and biological (age and weight) factors as well as those of technological (pre-slaughter, transportation, processing) conditions on rabbit carcass and meat quality (Dalle Zotte 2002), the results concerning the influence of natural substances (probiotics) or herbal extracts on rabbit meat composition have not yet been reported, except the oxidative stability of muscle tissues in rabbits (Botsoglou et al 2004). The antimicrobial effects of oregano and sage extracts are known (Marcin et al 2006;Simonová et al 2008); e.g.…”
mentioning
confidence: 99%
“…Increasing body reserves of antioxidants may help animals cope with the production of free radicals (oxidants) by eliminating the harmful effect of nitrate (Roth, 2000) and inhibiting the oxidation reactions (Botsoglou et al, 2004). In the literature, an adverse effect of nitrate in animal performance was observed at 600 to 700 ppm.…”
Section: Introductionmentioning
confidence: 99%